Cognitive mechanism of intimate interpersonal relationships and loneliness in internet-addicts: An ERP study. (December 2019) - Hou, Juan; Jiang, Yingying; Chen, Shuangyi; Hou, Yingying; Wu, Jingyi; Fan, Ning; Fang, Xiaoyi
Abstract: Interpersonal relationship and loneliness are important factors affecting internet addictive behavior of individuals. In the present study, we investigated intimate interpersonal relationships and loneliness in internet-addicts. We recorded event-related potentials (ERPs) of 32 internet addicts and 32 non internet-addicts. Participants viewed intimate-/conflict-relationship, happy/lonely, and neutral images. Results concerning attention probes showed that the accuracy rate of attention probes of internet-addicts was significantly lower than that of non internet-addicts; whereas, there was no significant difference in the reaction time of attention probes. Moreover, the differences in the mean amplitude and latency of P1, N1, N2P3, and LPP between internet-addicts and non internet-addicts were insignificant. Then, we found that the P1 amplitude of conflict images was significantly higher than that of intimate images among non internet-addicts; whereas internet-addicts indicated an insignificant difference between the two types of images. The P1 amplitude of lonely images was significantly higher than that of happy images among internet-addicts, but non internet-addicts were insignificant. The questionnaire data also obtained similar conclusions based on the EEG data. Finally, internet-addicts reported significantly higher loneliness scores than those of non internet-addicts. These results suggested that the social cognitive function of internet-addicts was probably impaired, especially in the cognition of interpersonal conflict. Furthermore, internet-addicts are likely to keep poor interpersonal relationships, which may induce more loneliness. Highlights: P1 of conflict images was significantly higher than that of intimate images among non internet-addicts, but internet-addicts were insignificant. P1 of lonely images was significantly higher than that of happy images among internet-addicts, but non internet-addicts were insignificant. Social cognitive function of internet-addicts was probably impaired, especially in the cognition of interpersonal conflict.